Brief communication: Improving lake ice modeling in ORCHIDEE-FLake model using MODIS albedo data - Z. Titus; Z. Titus; A. Cuynet; E. Salmon; C. Ottlé (The Cryosphere)
The FLake lake model embedded in the ORCHIDEE land surface model was recently updated to better represent winter ice cover. MODIS albedo data and the Great Lakes ice cover fraction dataset over the Laurentian Great Lakes were used to calibrate and validate a new parameterization of the lake albedo accounting for a partial ice cover fraction. The developments were validated for the phenology of the ice cover of 200 lakes of various sizes reported in the Global Lake and River Phenology Database. The results are in better agreement with the observations for all lake size categories, with the largest and deepest lakes showing more significant error reductions in the duration of the ice cover period up to 18 d. This study highlights the importance of considering partial ice cover to correctly model lake albedo in cold regions and thus to simulate realistic mass and energy exchanges at the land–atmosphere interface.